Understanding Restaurant Customers' Environmental Behavior in the Social Media Context: An Application of Theory of Planned Behavior - Unggul Kustiawan; Laksmi Pandansari (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
Social media users are now increasing, this makes social media to become an effective tool for companies to foster intentional consumer intentional behavior. This study uses the model of the theory of planned behavior to see its effect on intentional behavior on social media and also the moderating effect of economic rewards and social rewards and their effect on consumer offilne behavior. This quantitative research using the Structural Equation Model (SEM) method begins in 2023 by focusing on Z generation consumers in the food and beverage industry, especially franchise fast food restaurants in Indonesia. Data collection was carried out by distributing questionnaires online using Google Forms, which resulted in 166 respondents. Data analysis and processing using SmartPLS 3 software. The findings of this study indicate that, the planned behavior theory model consisting of attitude, subjective norm, and Perceived behavioral control can influence consumer intentional behavior even though attitude is proven not to have a significant effect. Economic reward and social reward are also proven to moderate the relationship between intentional behavior and offline consumer behavior. This research provides managerial implications for companies engaged in food and beverage, especially fast food restaurants, that want to contribute to making good changes to the world through the creation of certain activities or regulations published through social media.